The Challenge for Rapid Detection of High-Structured Circular RNA: Assay of Potato Spindle Tuber Viroid Based on Recombinase Polymerase Amplification and Lateral Flow Tests - Ivanov, Aleksandr V. (Plants (Basel), 2020)
An assay was developed to detect the potato spindle tuber viroid (PSTVd), a dangerous plant pathogen that causes crop damage resulting in economic losses in the potato agriculture sector. The assay was based on the reverse transcription and recombinase polymerase amplification (RT-RPA) of PSTVd RNA coupled with amplicon detection via lateral flow assay (LFA). Primers labeled with fluorescein and biotin were designed for RT-RPA for effective recognition of the loop regions in the high-structured circular RNA of PSTVd. The labeled DNA amplicon was detected using lateral flow test strips consisting of a conjugate of gold nanoparticles with antibodies specific to fluorescein and streptavidin in the test zone. The RT-RPA-LFA detected 10(6) copies of in vitro transcribed PSTVd RNA in reaction or up to 1:10(7) diluted extracts of infected plant leaves. The assay took 30 min, including the RT-RPA stage and the LFA stage. The testing of healthy and infected potato samples showed full concordance between the developed RT-RPA-LFA and quantitative reverse transcription polymerase chain reaction (RT-qPCR) and the commercial kit. The obtained results proved the feasibility of using the developed assay to detect PSTVd from a natural source.